Feasibility of MSMEs With SWOT Analysis Approach (Case Study at CV. Delta Raya, Sidoarjo) - Rieska Maharani; Sudarmiatin Sudarmiatin; Puji Handayati (Fakultas Teknik Universitas Maritim AMNI Semarang, 2025)
The increasingly competitive competition in international market is a challenge for Indonesia. In the development and economic growth, Small and Medium Industries (SMEs) play an important role. This study was conducted to find the most relevant marketing strategy so that sales at CV. Delta Raya, Sidoarjo, can increase. Based on the results of observations, CV. Delta Rata is in quadrant 1, which indicates a favorable situation. For CV. Delta Rata, because it has the strength that can be utilized as an opportunity to increase sales results. With this study, it is expected that business actors will improve the quality and quantity of optimal services, expand the market, and maximize the development of information technology.